Predation Scars Reveal Declines in Crab Populations Since the Pleistocene - Barclay, Kristina M.; Leighton, Lindsey R. (Frontiers in Ecology and Evolution, 2022)
Despite growing concerns over global fisheries, the status of most commercially exploited species are poorly understood. Fossil data provide pre-anthropogenic baselines for data-poor fisheries, yet are underutilized in fisheries management. Here we provide the first use of predation traces to assess the status of fisheries (crab). We compared crab predation traces on living individuals of the crab prey gastropod, Tegula funebralis, to Pleistocene individuals from the same regions in southern California. There were fewer crab predation traces on modern gastropods than their Pleistocene counterparts, revealing reductions in crab abundances today compared to the Pleistocene. We conclude that: 1) regardless of the cause, immediate actions are required to avoid further population reductions of commercially exploited crabs in southern California, 2) predation traces are a rapid, cost-effective method to assess otherwise data-poor fisheries, and 3) the inclusion of fossil data provides key new insights for modern resource and fisheries management.